Tackling social determinants of health through community based initiatives. Issue 7573 (19th October 2006) - Assai, M; Siddiqi, S; Watts, S
Abstract : Women are often the key to improving a population's health, and this is especially true in the Eastern Mediterranean region. Projects that empower women and provide basic needs are transforming poor communities